ANALISIS VISUAL GAMBAR ANAK PADA MASA PRA-SKEMATIK - Nuriarta I Wayan; Dwita Krisna Ari Ida Ayu; Suryawan I Gde (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2021)
This article aims to read visual signs and verbal signs by utilizing the children's drawings during the pre-schematic stage. The reading of the signs will be used to describe the elements of fine arts in the children's drawing. Four works of kindergarten children were chosen and observed. The four works are entitled "Mother", "Brother", "Zoo" and "Tree". These have been selected as the subjects of the study. These four works were chosen because these works were created by using different media, such as pencil on paper, watercolors on paper, and digital media. The object of this study is focused on visual analysis of the children's drawings on the elements of art, such as points, lines, shape, spaces, and colors. The pre-schematic stage is characterized by the appearance of circular images with lines that seem to indicate human or animal figures. During this stage, the scheme (the visual idea) is developed. The drawing shows what the child considers most important about the subject. There is a little understanding of space - objects are placed randomly throughout the image. The use of color is more emotional than logical. The elements of fine art are shown in the drawings can be described as the result of the observation 1) The lines have been controlled so has formed the image. 2) The shape of the object described has been identified as representing the object that the child wants to describe. 3) The colors used to fill the shapes are based on the child's imagination and desires except the color used to fill the shape of the tree. The colors of nature are the same as in real life, such as green leaves, blue sky, and green grass. In general, the image or drawing presented by the child is an illustration